2014
DOI: 10.1007/s00405-014-3029-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of peritonsillar abscess in patients over 40 years—a neglected age group

Abstract: The clinical presentation of peritonsillar abscess (PTA) in patients over 40 years is scarcely reported. Since older patients present differently than younger patients, our aim was to investigate possible correlation between illness severity in the older age group and their bacteriologic studies. A retrospective study on all cases of PTA admitted between June 1996 and June 2003 was carried out. Details regarding sex and age were obtained. Bacteriologic studies were analyzed for gram stain, aerobic and anaerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
2
8
2
Order By: Relevance
“…In the previous literature, recurrence rates after a first PTA episode are still unclear, ranging between 5 and 22 % in various studies, due partly to a limited number of patients, different methods of initial conservative treatment and marked differences in the follow-up period considered [1,4,7,13,19,20]. On the other hand, our data refer to a population of 2,667 patients, all treated with incision and drainage without tonsillectomy, and with an adequate follow-up.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In the previous literature, recurrence rates after a first PTA episode are still unclear, ranging between 5 and 22 % in various studies, due partly to a limited number of patients, different methods of initial conservative treatment and marked differences in the follow-up period considered [1,4,7,13,19,20]. On the other hand, our data refer to a population of 2,667 patients, all treated with incision and drainage without tonsillectomy, and with an adequate follow-up.…”
Section: Discussioncontrasting
confidence: 48%
“…There seem to be two pathogenically different PTA subtypes, one caused by a single organism, most often group A Streptococcus; the second polymicrobial, due to a variety of facultative and obligate anaerobes and probably representative of a chronic underlying microfloral imbalance. In patients aged 15-24 and in the elderly, Fusobacterium necrophorum is the prevalent pathogen [1][2][3][4] and its growth from PTA aspirates correlates with a higher rate of recurrence, and may serve as an additional relative indicator for tonsillectomy [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A Danish group showed that FN is often associated with younger patients . In previous studies, older age has been associated with certain bacterial species as well as more severe symptoms, which was also seen in our study. Smoking has been associated with older age and certain bacterial species; our results did not strengthen that.…”
Section: Discussionsupporting
confidence: 90%
“…There are speculations of different types of PTA; furthermore, age, gender, smoking status and dental health may have an impact on the clinical picture of the disease; accordingly, symptom renewal could be dependent on these factors. For example, in patients over 40 years of age, a lower percentage of aerobic bacteria have been detected, as well as the presence of more severe symptoms and clinical findings . Additionally, the type of pathogen may also determine the course of the disease .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation